Implementasi Pembelajaran Pendidikan Agama Islam Di Masa Pandemi Covid-19: Studi Kasus di SDN Tenggerkidul 2 Pagu Kabupaten Kediri - Zahro’, Fatimatuz (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
Abstrack In the era of the pandemic that hit the world at the beginning of 2020 until now, the learning process must continue to be carried out, even though it is online by all educational institutions throughout Indonesia. Likewise, at SDN Tenggerkidul 2, the implementation of online PAI learning also requires careful preparation so that it can run smoothly, and the objectives and learning outcomes can be achieved exactly as expected.On the basis of this background, the researchers asked the following research questions (1) How to plan PAI learning during the COVID-19 pandemic at SDN Tenggerkidul 2? (2) How is the implementation of PAI learning strategies and methods during the covid-19 pandemic at SDN Tenggerkidul 2? (3) How is the evaluation of PAI learning outcomes during the covid-19 pandemic at SDN Tenggerkidul 2?This research is a qualitative research accompanied by participant observation, in-depth interviews, and documentation. Meanwhile, for the analysis of research data using flow model analysis techniques which include; editing, namely checking or correcting the collected data. Organizing, is the rearrangement of the data that has been obtained in the research needed in the framework of the exposure that has been planned with the formulation of the problem systematically. Analyzing, namely by analyzing the data that has been obtained from research to obtain conclusions about the truth of the facts found, which in the end is an answer to the formulation of the problem. The results of the study, namely: (1) The learning planning used during the covid-19 pandemic at SDN Tenggerkidul 2 was to prepare the completeness of online learning administration by utilizing the existing infrastructure. (2) The implementation of PAI learning strategies and methods during the covid-19 pandemic at SDN Tenggerkidul 2 was carried out online and offline using various methods and learning strategies. (3) Even during the Covid-19 pandemic, the results of the evaluation of student learning are quite good, because parents are increasingly paying attention to the implementation of learning and the tasks that their children have to do every day. Keywords: PAI Implementation, During the Covid-19 Pandemic Abstrak